2012
DOI: 10.1159/000334086
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC1, MUC2, MUC5AC and MUC5B in Mucinous Lesions of the Breast

Abstract: Objective: The purpose of this study was to investigate the expression of MUC1, MUC2, MUC5AC and MUC5B in breast mucinous lesions. Methods: Immunohistochemical staining of MUC1, MUC2, MUC5AC, MUC5B and synaptophysin was performed in 78 cases of mucinous carcinoma (MC), 36 cases of mucocele-like lesions (MLL) and 13 cases of solid papillary carcinoma (SPC). MC was classified as type A or type B and MLL was classified as MLL, MLL with atypical ductal hyperplasia and MLL with ductal carcinoma in situ. Results: MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…It was however observed that MUC1-positive cases were predominantly of higher grades (Table 4). is contrasts the published literature on western cases, where MUC1 positivity is often associated with lower histological grades [32,[34][35][36]. Again, no significant association was observed between MUC1 overexpression and Ki-67, yet MUC1-overexpressing cases were predominantly of high Ki-67 indexes, suggesting higher mitotic activities in these tumours.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…It was however observed that MUC1-positive cases were predominantly of higher grades (Table 4). is contrasts the published literature on western cases, where MUC1 positivity is often associated with lower histological grades [32,[34][35][36]. Again, no significant association was observed between MUC1 overexpression and Ki-67, yet MUC1-overexpressing cases were predominantly of high Ki-67 indexes, suggesting higher mitotic activities in these tumours.…”
Section: Discussioncontrasting
confidence: 91%
“…Although HER2 overexpression tumours are generally sensitive to trastuzumab therapy, they are inherently aggressive, with high proliferative rates, high histological grades, and frequent lymph node metastasis [43,44]. None of the previous Western studies which were reviewed reported a significant association between MUC1 expression and HER2 overexpression [33,34,36]. Elseed et al [40] made no report on the association between MUC1 and HER2 expression, as their study focused only on ER status and the triple negative phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type A showed luminal/apical expression of MUC1 and MUC2, while type B showed membrano-cytoplasmic expression of MUC1 and MUC2. Type A was negative for MUC5B, while type B showed membrano-cytoplasmic expression of MUC5B [26]. Such differences in the intrinsic characteristics of type A and B mucinous carcinoma may contribute to the difference in tumor microenvironments, which would create distinct differences in MCT4 stromal expression.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies regarding the correlation between MUC1 expression and the histological grade of breast carcinoma, which showed different results, including according to a study conducted by Manu et al, who found that there was no significant correlation between positive-expressed MUC1 and histological grade, although there was a tendency for MUC1 to be expressed positively, that cases with positive MUC1 expression were dominated by higher grades [6]. This contrasts with studies conducted by Kim et al, Syed et al, and Do et al, which showed that positive MUC1 expression was often associated with a lower grade of breast carcinoma [13][14][15].…”
Section: Introductionmentioning
confidence: 87%